Earnings management among industries: between the old and new economies - Sadowski, Adam; Comporek, Michał; Osińska, Magdalena; Walińska, Ewa; Engelseth, Per (Technological and Economic Development of Economy, 2025)
This paper investigates sectoral prevalence and patterns of accrual-based earnings management in public companies listed on the Warsaw Stock Exchange. This research introduces a novel perspective by analysing differences in discretionary accruals proxies among industries, with particular emphasis on statistical variation of the earnings management through accruals in the old and new economies companies. Moreover, this paper fills a research gap in the literature regarding a shortfall of broader analyses on the industry-specific attributes explaining earnings management behaviours. Our findings confirmed that the extent of accrual-based earnings management in public companies varies significantly depending on the industry in which they operate. We demonstrated that companies from the new economy industries and those operating in less concentrated markets engaged in accrual-based earnings management practices more than others. On the other hand, we did not find a statistically significant relationship between the accounting-type earnings management and company-specific product market power from the perspective of the pooled sample and subsamples characterized by the specific directions of earnings games.